Development of problem based learning student worksheets on human digestive system materials to increase students learning outcome - Dhea FujaRahmawi Nasution; Rasyidah Rasyidah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
The lack of learning media for biology material in high school, so it is necessary to develop a PBL-based student worksheet as a learning media. This research aims to develop PBL-based student worksheets that are appropriate, practical, and effective in improving student learning outcomes. This study uses the ADDIE model. Quantitative data analysis examines the level of feasibility, practicality, and effectiveness. Meanwhile, qualitative research can be obtained from observations, criticisms, comments, and suggestions. The student worksheet developed meets the valid criteria to be tested with revisions. The practicality of student worksheets also obtained very practical criteria according to the teacher I and practical criteria according to teacher II. The practicality of this student worksheet also got practical criteria for the responses of class XI IPA1 students and was very practical on the responses of class XI IPA2 students. The development of student worksheets is also said to be effective based on the completeness of the pre-test and post-test results of class XI IPA1 and XI IPA2 students, namely the high category. So these results can be concluded that the developed PBL-based student worksheet is declared valid, practical, and effective. These results also show PBL-based student worksheets can also improve student learning outcomes.AbstrakMinimnya media pembelajaran materi biologi di SMA, sehingga perlu pengembangan LKPD berbasis PBL sebagai media pembelajaran. Tujuan penelitian ini mengembangkan LKPD berbasis PBL yang tepat, praktis dan efektif untuk  meningkatkan hasil belajar siswa. Penelitian ini menggunakan model ADDIE. Analisis data kuantitatif mengkaji tingkat kelayakan, kepraktisan, dan efektivitas. Sementara itu, analisis kualitatif dapat diperoleh dari pengamatan, kritik, komentar dan saran. Pengembangan LKPD memenuhi kriteria valid untuk diuji dengan revisi. Kepraktisan LKPD memperoleh kriteria sangat praktis menurut guru I dan kriteria praktis menurut guru II. Kepraktisan LKPD ini juga memperoleh kriteria praktis untuk respon siswa kelas XI IPA1 dan sangat praktis untuk respon siswa kelas XI IPA2. Pengembangan LKPD juga dikatakan efektif berdasarkan ketuntasan hasil pre-test dan post-test siswa kelas XI IPA1 dan XI IPA2 yaitu kategori tinggi. Sehingga hasil tersebut dapat disimpulkan bahwa LKPD berbasis PBL yang dikembangkan dinyatakan valid, praktis, dan efektif. Hasil ini juga menunjukkan LKPD berbasis PBL juga dapat meningkatkan hasil belajar siswa.